A genomic epidemiological study shows that prevalence of antimicrobial resistance in Enterobacterales is associated with the livestock host, as well as antimicrobial usage. Issue 10 (5th October 2021) - AbuOun, Manal; Jones, Hannah; Stubberfield, Emma; Gilson, Daniel; Shaw, Liam P.; Hubbard, Alasdair T. M.; Chau, Kevin K.; Sebra, Robert; Peto, Tim E. A.; Crook, Derrick W.; Read, Daniel S.; Gweon, H. Soon; et al.
Abstract : Enterobacterales from livestock are potentially important reservoirs for antimicrobial resistance (AMR) to pass through the food chain to humans, thereby increasing the AMR burden and affecting our ability to tackle infections. In this study 168 isolates from four genera of the order Enterobacterales, primarily Escherichia coli, were purified from livestock (cattle, pigs and sheep) faeces from 14 farms in the United Kingdom. Their genomes were resolved using long- and short-read sequencing to analyse AMR genes and their genetic context, as well as to explore the relationship between AMR burden and on-farm antimicrobial usage (AMU), in the three months prior to sampling. Although E. coli isolates were genomically diverse, phylogenetic analysis using a core-genome SNP tree indicated pig isolates to generally be distinct from sheep isolates, with cattle isolates being intermediates. Approximately 28 % of isolates harboured AMR genes, with the greatest proportion detected in pigs, followed by cattle then sheep; pig isolates also harboured the highest number of AMR genes per isolate. Although 90 % of sequenced isolates harboured diverse plasmids, only 11 % of plasmids ( n =58 out of 522) identified contained AMR genes, with 91 % of AMR plasmids being from pig, 9 % from cattle and none from sheep isolates; these results indicated that pigs were a principle reservoir of AMR genes harboured by plasmids and likely to be involved in their horizontal transfer. Significant associations were observed between AMU (mg kg −1 ) and AMR. As both the total and the numbers of different antimicrobial classes used on-farm increased, the risk of multi-drug resistance (MDR) in isolates rose. However, even when AMU on pig farms was comparatively low, pig isolates had increased likelihood of being MDR; harbouring relatively more resistances than those from other livestock species. Therefore, our results indicate that AMR prevalence in livestock is not only influenced by recent AMU on-farm but also livestock-related factors, which can influence the AMR burden in these reservoirs and its plasmid mediated transmission.